Estimation of evaporation rate of water droplet group in spray drying process. (14th December 2020) - Okada, Sayaka; Ohsaki, Shuji; Nakamura, Hideya; Watano, Satoru
Graphical abstract: Highlights: Numerical simulations of the spray drying process were performed. The validity of the simulation was verified based on experimental data. The evaporation rate of droplet group strongly depends on the driving force for evaporation. The effects of operation and droplet conditions on evaporation rate were investigated. A method for estimating evaporation rate of droplet group based on operating conditions was proposed. Abstract: Spray drying is a fundamental process in several industries. As many factors affect the particulate product property in complex manners, optimal operating conditions have been determined through trial and error. In a spray dryer, numerous sprayed droplets form a tear-shaped droplet aggregate (droplet group), in which each droplet evaporates at a different rate. Owing to the complicated evaporation behavior of a droplet group, a detailed mechanism of dried particle generation has yet to be sufficiently elucidated. The objective of this study is to investigate the effects of the operating conditions of spray drying processes on the evaporation rate of a droplet group. Numerical simulations were performed under various conditions to calculate the evaporation rates of a droplet group in a spray drying process. A method for estimating the evaporation rate of a droplet group based on the operating conditions, using the thermal efficiency and Nusselt number, is proposed.